Evaluation of Site-Specific Methane Emission Factors from Biogas Production in Tapioca Industrial Wastewater Treatment Systems - Eva Martha Pratiwi; Dewi Agustina Iryani; Rahmat Safe'i; Agus Haryanto; Samsul Bakri; Udin Hasanudin (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Tapioca processing in Indonesia generates high-strength wastewater that can emit substantial methane (CH4) without sufficient treatment. The objective of this study is to determine a site-specific methane emission factor (B₀) for biogas power generation based on an anaerobic covered lagoon (ACL) and compares it with the IPCC default. Research was conducted on biogas power plant based on cassava wastewater with a capacity of 2 × 1.5 MW in Central Lampung. Twenty-two months of full-scale monitoring database included wastewater flow, COD, biogas yield volume, and methane concentration across wet and dry seasons. The results show that covered anaerobic lagoon systems with biogas recovery can effectively reduce fugitive methane. Using AMS-III.H and IPCC methods, a strong linear relationship between methane production and COD removal produced a site-specific B₀ of 0.2302 kg CH4/kg COD (0.321 m3 CH4/kg COD), slightly below the IPCC value. Lower yield was likely influenced by seasonal dilution, operational variability, and partial degradation of cassava-based organics. Results of this research emphasize the need for site-specific emission factors to improve Indonesia’s GHG inventories and mitigation strategies.